Tinjauan Yuridis Pertanggungjawaban Pidana Terhadap Calon Tenaga Kesehatan Akibat Kesalahan Dalam Tindakan Medis - SAMARA, SYNTHIA; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Criminal liability can not be discharged from the discussion of a criminal act. It is impossible for a person to be convicted or liable if the person does not commit a crime. The person must take criminal liability if he has made a mistake. Thus, the occurrence of criminal liability because there has been a crime committed by a person. Doctor Co-ast devote themselves in the health field and have sufficient knowledge and skills to make health efforts. The young doctor is a medical graduate student who follows the medical coercion counselor's office to obtain a medical profession degree. In this case, many of us see there are some hospitals that use the services of Doctor Co-ast. There are, however, some doctors in hospitals who use the services of a Young Doctor or Doctor Co-ast in dealing with the patient if the Doctor is not in place or is examining another patient. However, looking at some examples of cases, there has been an omission done by the dokter co-ast in the hospital he placed but the negligence is not yet known how the accountability of the hospital itself and also from the young doctor. The problems and objectives that will be discussed in this thesis is to know how the criminal responsibility of the candidate of health worker and the hospital for negligence in the medical action done by the prospective health worker.This type of research is normative juridical, because in this study the authors match or evaluate a decision to the law that has been valid, the source data used, primary data, secondary data and tertiary data, data collection techniques in this study by interview and literature study .From the results of this study it can be concluded that the mistakes made by doctor co-ast directly related to the doctor as a party yag party can be held legally accountable that does not show the activities of the young doctor's office during his learning activities in the hospital. And if the occurrence of an action in the form of negligence, then the party responsible for such negligence is the supervisor of the hospital.Keywords: Accountability - Criminal - Medical Personnel - Medical Actions